Zé Pereira: a performance carnavalesca em Itaberaí-GO - Faria, Marcelo Fecunde de (2015)
This dissertation deals with the carnival manifestation "Zé Pereira" in Itaberai- GO, analyzing it as a cultural performance adopting some concepts present in studies of cultural performances to understand how is the relationship and involvement that are coming and characteristic of performative action, linking the liminality concepts of Victor Turner, the theory of performance of Richard Schechner, Bakhtin and DaMata Carnival. The focus of the analysis are the events that take place 15-17 days before the national carnival, being a predecessor activity the carnival period, the performance is formed by a group of masked young people wearing horrifying masks, accompanied by a drumming group with several instruments percussion and prepared by a committee of support organization, all these characters are surrounded by an audience that accompanies the demonstration during ALL the days passing through different streets of the city gaining attention from citizens who are in their homes. This work aims to demonstrate that while performance “Zé Pereira” produces historical, social and cultural repercussions on people directly or indirectly involved. This context was accompanied by ethnographic experience and observation of the process of formation and constitution of the current “Zé Pereira” in Itaberaí.